FENOMENA PEMBACAAN KITAB AQIDATUL AWAM DAN RELEVANSINYA TERHADAP NILAI SPIRITUAL SANTRI DI PONDOK PESANTREN SABILUL MUHTADIN DI DESA LANGKAN - Dwi Putri; Nur Fitriyana; Ahmad Soleh Sakni (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2021)
Kitab Aqidatul Awam is one of the books of tauhid, which explains the oneness and essence of Allah swt, the angels, the prophets and messengers. In this case, the Aqidatul Awam book is not only studied as a subject but also practiced by reading it every day after the midday call to prayer and before performing the midday prayer by the students of the Sabilul Muhtadin Islamic Boarding School. This is what makes the writer interested in examining the phenomenon of the relationship between the practice of the Aqidatul Awam book and the spiritual values ​​felt by the students when reading the Aqidatul Awam book. The type of research used is field research using qualitative methods. The primary data source in this case is the Aqidatul Awam book and the students of the Sabilul Muhtadin Islamic Boarding School. While secondary sources are various relevant sources such as theses, articles, journals, books, documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results showed that the phenomenon of the practice of reading the book of Aqidatul Awam was carried out by the students of the Sabilul Muhtadin Islamic Boarding School after the call to prayer for midday. This is done because the time of dzuhur is understood as a good time and afdhal to do good deeds. The relevance of the practice of reading the book of Aqidatul Awam to the spiritual value of students who practice it istiqamah, namely they can feel peace of mind, feel closeness to Allah swt and remind them to always do good.